The role of mindfulness in harmonising sustainable lifestyles. (2nd January 2018) - Tobin, Kenneth
ABSTRACT: I begin with a review of our research on meditation, mindfulness, expressed emotions, and physiological variability while teaching. Then, through the theoretical lenses of polyvagal theory, I examine an event from our ongoing research in which a teacher had very low levels of blood oxygenation. Apparently, her body switched from parasympathetic to sympathetic functioning. As well as changes in prosody and facial expression of emotion being consistent with her body operating in a fight/flight mode, the teacher also was breathing through her mouth. This led to an intensive review of studies on breathing and the production of nitric oxide in humans, its benefits, and the desirability of breathing in and out through the nose. Based on what I learned from our empirical work and a review of literature, I designed two interventions – a breathing heuristic and a meditation activity that incorporates nasal breathing and humming during the outbreath.